Expression changes of antioxidant, apoptotic, anti-apoptotic genes and miR-15b-34a-21-98 in over tissue by using erythromycin, quinacrine and tetracycline in non-surgical sterilization - Kara, Murat; Yumrutas, Onder; Atilgan, Remzi; Baspinar, Melike; Sapmaz, Ekrem; Kuloglu, Tuncay (Springer, 2014)
In the present study, effects on expression of antioxidant, apoptotic and anti-apoptotic genes (GSR, GRX3, SOD1, RAI-NOS, HSP7, BAX, Bc1-2, CASP3 and MDH1) of substances being used in non-surgical sterilization such as quinacrine, erythromycin and tetracycline were evaluated in over tissue. Moreover, expression of some specific mi-RNA (miR-15b, miR-21, miR34a and miR-98) that playing a role in apoptosis was determined in same tissue. Prospective comparative experimental study. Genetics and Histology laboratory. Total number of 28 Wistar albino 12-14 week old female rats with regular cycles and 200-220 grams in weight. Total RNA was isolated from tissues by using a RNA isolation kit. Gene expression levels were evaluated by Real-Time PCR method. Tubal passage and fibrosis induction in tissues was observed in the histochemical analysis. In the statistical analysis of data Kruskal Wallis variance analysis and Mann Whitney U test were used and p <0.05 were accepted as significant. While the expressions of target genes found to be increased in quinacrine and erythromycin group when compared to control group, this increase was insignificant. In quinacrine group, increase in the SOD1 expression levels was only statistically significant (p <0.05). Expression levels of miR-15b, miR-21, miR34a and miR-98 microRNAs were found to be upregulated in all experimental groups, despite this, only the increased expression miR-34 was found as statistically significant when compared to control. Tubal blockage and fibrosis induction scores of quinacrine, erythromycin and tetracycline were significantly higher than control. Results of the present study suggest that the doses treated of quinacrine, erythromycin and tetracycline used in nonsurgical sterilization effect poorly the expression of antioxidant, apoptotic and anti-apoptotic genes, but the expression of miR-34 playing the role in apoptosis increased after treatment of these substances.
Keywords: Non-surgical sterilization; Quinacrine; Erythromycin; Tetracycline; miRNA